Case Report on Horner?s Syndrome Following Thyroidectomy - Ahmad Zeeshan Jamil, Syeda Sidra Gillani (Pakistan Journal of Ophthalmology, 2019)
We report a case of 37-year-old Pakistani Punjabi woman who visited the Eye department of DHQ teaching hospital Sahiwal with complaint of drooping of right upper eyelid following the thyroidectomy. This is to highlight the importance of proximity of Thyroid gland and sympathetic trunk. Hence, to make surgeon more vigilant to avoid risk of injury to sympathetic trunk so that potentially stressing cosmetic disfigurement can be avoided. Moreover, this would help the surgeon to undertake measures to lessen the risk of injuring the sympathetic runk while doing the thyroidectomy. Key words: Horner’s syndrome, miosis, ptosisthyroidectomy.